(3JfbjM GdCHMGK ddedd GdKdGKs - (3GHf cehfI, YR GdOhdI, SYO Hf efUhQ Hf SYO, YR GdOhdI, J (B683(3g` (B1284(3es
(3ChdgG (B:s
(3ChdgG(B: (3CMeO Gddg Ydi eG CQTO hgOi (B... (3GdHGH GdChd aj HjGf MbjbI GdfHhI hbjGegG hEKHGJ hLhOgG hefGaYgGs
(3BNQgG (B:s
(3BNQgG(B: (3hbO YQaJ eG jbGd aj Pdc hbO WYf HeWGYf cKjQI hCLHJ YfgG hjMJed GdehVY eHGMK CNQi hdcfj dG COQj (B.. (3ajaj gPG GdbOQ GdPj PcQJg hef Gddg JYGdi SHd GdgOGjI hGdYUeI hMSf GdNGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 102s
(3GdPQjYI, L (B4: 334s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds